Association of serum neurofilament light and disease severity in patients with spinocerebellar ataxia type 3. (1st December 2020) - Peng, Yun; Zhang, Youming; Chen, Zhao; Peng, Huirong; Wan, Na; Zhang, Jennifer; Tang, Jingyi; Wang, Puzhi; Xie, Yue; Cai, Qiyong; Liu, Shaohui; Zhang, Xuewei; et al.
Abstract : Objective: To investigate serum neurofilament light protein (sNfL) levels in patients with spinocerebellar ataxia type 3 (SCA3) and to determine whether they are associated with disease severity. Methods: This cross-sectional study enrolled 185 healthy controls and 235 ATXN3 mutation carriers (17 asymptomatic stage, 20 preclinical stage, and 198 ataxic stage). We measured sNfL levels with the single molecule array (Simoa) platform. Clinical disease severity was assessed using the Scale of Assessment and Rating of Ataxia (SARA) and the Inventory of Nonataxia Signs (INAS). In a subgroup of 50 ataxic stage patients, we further evaluated the gray matter volume and the integrity of white matter fibers by MRI. Results: sNfL concentrations were elevated in asymptomatic, preclinical, and ataxic ATXN3 mutation carriers compared to controls (12.18 [10.20–13.92], 21.84 [18.37–23.45], 36.06 [30.04–45.90], and 8.24 [5.92–10.84] pg/mL, median [interquartile range], respectively, p < 0.001). sNfL correlated with SARA ( r = 0.406, 95% confidence interval [CI] 0.284–0.515, p < 0.0001) and INAS ( r = 0.375, 95% CI 0.250–0.487, p < 0.0001), and remained significant after adjustment for age and CAG repeats. In addition, we observed negative correlations of the sNfL with gray matter volume in the left precentral gyrus and the left paracentral lobule as well as with the mean diffusivity in widespread white matter tracts. Conclusion: Our results demonstrate that sNfL levels are increased in SCA3 and are associated with clinical disease severity, which supports sNfL as a biomarker for disease severity in SCA3. Classification of evidence: This study provides Class II evidence that in patients with SCA3, sNfL elevations are associated with clinical disease severity.